The Market for Safety Regulation and the Effect of Regulation on Fatalities: The Case of Motorcycle Helmet Laws - Sass, Tim R.; Leigh, J. Paul (The Review of Economics and Statistics, 1991)
Tim R. Sass, J. Paul Leigh, The Market for Safety Regulation and the Effect of Regulation on Fatalities: The Case of Motorcycle Helmet Laws, The Review of Economics and Statistics, Vol. 73, No. 1 (Feb., 1991), pp. 167-172